Impact of Intraoperative Ocular Lubricants on Corneal Debridement Rate During Vitreoretinal Surgery - Mathison ML (Dove Medical Press, 2020)
Michael L Mathison,1 Albert S Li,1 Yicheng K Bao,2 Andrew JW Huang,1 Rithwick Rajagopal1 1Department of Ophthalmology and Visual Sciences, Washington University School of Medicine, Saint Louis, MO 63110, USA; 2Department of Medicine, University of Missouri — Kansas City School of Medicine, Kansas City, MO 64112, USACorrespondence: Rithwick RajagopalWashington University School of Medicine, Campus Box 8096, 660 South Euclid Avenue, Saint Louis, MO 63110, USATel +1 314 362 6929Fax +1 314-362-2420Email rajagopalr@wustl.eduPurpose: To compare surgical parameters among patients receiving Viscoat (sodium chondroitin sulfate 4%–sodium hyaluronate 3%) or Goniosol (hydroxypropyl methylcellulose 2.5%) as topical lubricants for retinal surgery.Methods: This was a retrospective analysis of patients undergoing retinal surgery between March 2013 and March 2018 using Goniosol or Viscoat as adjuvants. Primary outcome measures were rate of corneal debridement and operative time between groups, compared using χ2 and t-tests, respectively.Results: Compared to Viscoat (n=319), the Goniosol group (n=210) had more frequent intraoperative corneal debridement (21.4% vs 0, p<0.05) and longer surgical times (98 vs 78 minutes, p<0.05). Patients in the Viscoat group had higher rates of complex procedures (34.8% vs 26.7%, p<0.05), but were younger (50.7 vs 55.0 years, p<0.05) and more likely to be phakic (83.4% vs 70.5%, p<0.05).Conclusion: These findings suggest potential advantages of using Viscoat over Goniosol for corneal lubrication to aid visualization during vitreoretinal surgery.Keywords: corneal epithelium, corneal debridement, corneal edema, Goniosol, Viscoat, vitreoretinal surgery